Mutations linked to the pro alpha 2(I) collagen gene are responsible for several cases of osteogenesis imperfecta type I. Issue 5 (October 1986) - Wallis, G; Beighton, P; Boyd, C; Mathew, C G
Abstract : We have analysed six South African families with osteogenesis imperfecta type I using three DNA polymorphisms associated with the pro alpha 2(I) collagen gene. In four of these families linkage of the pro alpha 2(I) gene and the osteogenesis imperfecta phenotype was suggested, whereas in the remaining two families there was a lack of linkage. No distinct correlation could be made between the phenotypic features of the families studied and linkage or lack of linkage to the pro alpha 2(I) gene. Two different haplotypes were found to be associated with the mutant pro alpha 2(I) alleles. These findings suggest that molecular heterogeneity exists within osteogenesis imperfecta type I and that in a significant proportion of cases the defect is linked to the pro alpha 2(I) gene.